2014
DOI: 10.1631/jzus.a1400165
|View full text |Cite
|
Sign up to set email alerts
|

Interactions between engineered nanomaterials and agricultural crops: implications for food safety

Abstract: Engineered nanomaterials (ENMs) are being discharged into the environment and to agricultural fields, with unknown impacts on crop species. In this paper, we review the literature on ENMs uptake, translocation/distribution, and generational transmission in various crop species, as well as potential material trophic transfer. Previous studies reveal that ENM-exposed crops exhibit adaptive processes in response to stress, including endocytosis/endosome activities, production of antioxidant enzymes, regulation of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
57
0
5

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 117 publications
(62 citation statements)
references
References 135 publications
(175 reference statements)
0
57
0
5
Order By: Relevance
“…Although a number of publications have begun to explore the interaction between NPs and plants (Rico et al, 2011;Deng et al, 2014;Ma et al, 2010;Priester et al, 2012;Majumdar et al, 2015;Musante and White, 2012), the knowledge of the implications of NPs on the nutritional value of crop fruit is still limited. Rico et al showed that nCeO 2 decreased some of the nutrients in rice grains, including Fe, S, prolamin, glutelin, lauric and valeric acids, and starch.…”
Section: Introductionmentioning
confidence: 99%
“…Although a number of publications have begun to explore the interaction between NPs and plants (Rico et al, 2011;Deng et al, 2014;Ma et al, 2010;Priester et al, 2012;Majumdar et al, 2015;Musante and White, 2012), the knowledge of the implications of NPs on the nutritional value of crop fruit is still limited. Rico et al showed that nCeO 2 decreased some of the nutrients in rice grains, including Fe, S, prolamin, glutelin, lauric and valeric acids, and starch.…”
Section: Introductionmentioning
confidence: 99%
“…Several mechanisms such as the production of intracellular oxidative stress, mechanistic damage, and changes in nutrient elements levels were suggested based on the experimental observations to interpret the toxicity and damage of nanoparticles to animals, microbes, and plants (Miralles et al, 2012;Sharifi et al, 2012;Podila and Brown, 2013;Deng et al, 2014).…”
mentioning
confidence: 99%
“…Debates widely exist in literature. A number of knowledge gaps and challenges are still waiting to be addressed (Sharifi et al, 2012;Podila and Brown, 2013;Deng et al, 2014;Luo et al, 2014;Kumar et al, 2014).…”
mentioning
confidence: 99%
See 2 more Smart Citations